AGEs–RAGE overexpression in a patient with smoking-related idiopathic nodular glomerulosclerosis - Nakamura, Nao (CEN Case Rep, 2017)
We report a case of smoking-related idiopathic nodular glomerulosclerosis (ING) with overexpression of glomerular advanced glycation end products (AGEs) and their receptor (RAGE). A 59-year-old Japanese man with nephrotic syndrome, who had a smoking history of one pack of cigarettes per day for approximately 40 years, presented with a 3-year history of urinalysis abnormalities without clinical evidence of diabetic mellitus. The patient’s leg edema progressively worsened over the previous 2 years, and he was admitted to our hospital. Renal biopsy showed mesangial expansion with diabetic Kimmelstiel–Wilson-like nodular lesions, glomerular basement thickening, and arteriosclerosis. No electron-dense deposits, fibrils, or microtubule deposits were seen in the glomeruli on electron microscopy. Skin AGE level measured using AGE reader was higher in this case than the average level in age-matched Caucasians. In addition, immunohistochemical analysis revealed that N-carboxymethyl lysine, one of the major AGEs, and RAGE were overexpressed and podocin expression was decreased in the peripheral area of the glomerular nodular lesions. These observations suggest that AGEs–RAGE system may be activated in smoking-related ING, possibly leading to the progression of renal dysfunction.